2009
DOI: 10.1002/adsc.200800614
|View full text |Cite
|
Sign up to set email alerts
|

The Aerobic Oxidative Cleavage of Lignin to Produce Hydroxyaromatic Benzaldehydes and Carboxylic Acids via Metal/Bromide Catalysts in Acetic Acid/Water Mixtures

Abstract: Roughly 30% of all woody plants is composed of lignin. Five different lignin samples, from wood and bagasse, were oxidized in air with a cobalt/ manganese/zirconium/bromide (Co/Mn/Zr/Br) catalyst in acetic acid as a function of time, temperature, pressure, and lignin and catalyst concentrations. 18 products were identified via gas chromatographymass spectrometry (GC/MS). The most valuable products from lignin were 4-hydroxybenzaldehyde, 4-hydroxybenzoic acid, 4-hydroxy-3-methoxybenzaldehyde (vanillin), 4-hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(72 citation statements)
references
References 25 publications
1
71
0
Order By: Relevance
“…Catalysts used in lignin oxidation range from metalsupported alumina catalysts like Pd/Al 2 O 3 [107] and Cu-Ni/ Al 2 O 3 [108] to a wide variety of homogenous catalysts [89,109]. Metal salt-based catalysts such as CuO, CuSO 4 , FeCl 3 , and MnSO 4 are the most frequently reported catalysts for lignin oxidation, usually using molecular oxygen as oxidant [33,36,110]. Tab.…”
Section: Catalysts In Lignin Conversionmentioning
confidence: 99%
“…Catalysts used in lignin oxidation range from metalsupported alumina catalysts like Pd/Al 2 O 3 [107] and Cu-Ni/ Al 2 O 3 [108] to a wide variety of homogenous catalysts [89,109]. Metal salt-based catalysts such as CuO, CuSO 4 , FeCl 3 , and MnSO 4 are the most frequently reported catalysts for lignin oxidation, usually using molecular oxygen as oxidant [33,36,110]. Tab.…”
Section: Catalysts In Lignin Conversionmentioning
confidence: 99%
“…The most valuable products from lignin were 4-hydroxybenzaldehyde, 4-hydroxybenzoic acid, 4-hydroxy-3-methoxybenzaldehyde (vanillin), 4-hydroxy-3-methoxybenzoic acid (vanillic acid), 4-hydroxy-3,5-dimethoxybenzaldehyde (syringaldehyde), and 4-hydroxy-3,5-dimethoxybenzoic acid (syringic acid). By the use of model compounds they demonstrated that (i) the presence of the phenolic functionality on an aromatic ring does inhibit the rate of reaction but that the alkyl group on the ring is still oxidized to the carboxylic acid; (ii) the masking of phenol by acetylation occurs at a reasonable rate in acetic acid; (iii) the alkyl group of the masked phenol is very readily oxidized; (iv) an acetic anhydride/acetic acid mixture is a good oxidation solvent; and (v) that a two-step acetylation/oxidation to the carboxylic acid is feasible [106]. Crestini et al had reported a convenient and efficient application of heterogeneous methyl-rhenium trioxide (MTO) systems for the selective oxidation of lignin model compounds and lignin [36].…”
Section: Lignin To Phenolic Acidsmentioning
confidence: 98%
“…Based on the different structure of the lignin precursors, the oxidation reaction pathways can be divided into three categories. First, p-coumaryl alcohol resembling lignin model compounds to 4-hydrobenzaldehyde [18,26,41,43] and then 4-hydrobenzoic acid [106]; Second, coniferyl alcohol resembling lignin model compounds to vanillin [9,81] and vanillic acid [36]; Third, sinapyl alcohol resembling lignin model compounds to syringaldehyde and syringic acid.…”
Section: Lignin To Phenolic Acidsmentioning
confidence: 99%
“…In the limited literature for the degradation of lignin, [18][19][20][21][22][23][24][25] Sergeev and Hartwig 26 made impressive progress on selective hydrogenolysis of lignin model compounds catalyzed by a soluble nickel carbene complex under relatively mild conditions. Kou and co-workers 27 also did nice work on hydrocraking of wood lignin over various noble-metal catalysts through a twostep hydrogenation process, they obtained about 42 wt% C 8 -C 9 alkanes and 10 wt% C 14 -C 18 alkanes from wood lignin.…”
Section: Introductionmentioning
confidence: 99%